Sebuah Wacana Progresifitas Karawitan Jawa, Nilai dan Harapan - FX. Purwa Askanta (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2006)
Ivowaaay industrial music has no! been thought as an unvaluable kind of music anymore because it has become the need of society or certain community. The excistence of industrial music is a part of a long history of music development, and it finds the character, which is to be able to have its mean, and has been looked for in certain porpuse Owing to the fact that nowadays situation slows down the development and the excistence of traditional .Javanese karawitan, it is necesary that the progresivity and inovac)’ of karawitan has to be directed to an industrialization.Keywords:   Industrial music, valuie, tradition